Congenital insensitivity to pain with anhidrosis and compensatory hyperhidrosis - Aradhana Rout; Sandeep Arora; Shamsher Singh Dalal; Sudeep Kumar (Wolters Kluwer Medknow Publications, 2021)
Hereditary sensory and autonomic neuropathy is a rare syndrome characterized by congenital insensitivity to pain, temperature changes, and an autonomic nerve formation disorder. We report an 8-year-old boy who presented with late-onset of self-mutilating behavior, insensitivity to pain, temperature, and anhidrosis with compensatory hyperhidrosis. Exome sequencing revealed a mutation of the SCN9A gene at chromosome 2 with nucleotide change c. G554A/p. Arg185His at exon 5 along with HSPB1 mutation at chromosome 5.